SNARC Effect in Different Effectors. (January 2016) - Hesse, Philipp N.; Fiehler, Katja; Bremmer, Frank
The SNARC (spatial numerical association of response codes) effect, indicating that subjects react faster to the left for small numbers and to the right for large numbers, is used as evidence for the idea that humans use space to organize number representations. Previous studies compared the SNARC effect across sensory modalities within participants and concluded modality independence. So far, it is unknown what sensory-to-motor mappings are involved in generating the SNARC effect and whether these mappings are identical for different effectors within subjects. Hence, we tested whether the SNARC effect is effector specific. Participants performed an auditory parity judgment task and responded with three different effectors: finger (button release), eyes (saccades), and arm (pointing). The SNARC effect occurred in each effector but varied in strength across the effectors. Across subjects, we found a significant correlation of SNARC strength for finger and arm responses suggesting the use of a shared sensory-to-motor mapping. SNARC strength did not correlate, however, between finger and eyes or arm and eyes. An additional statistical analysis based on conditional probabilities provided further evidence for SNARC-effector specificity. Taken together, our results suggest that the sensory-to-motor mapping is not as tight as it would be expected if the SNARC effect was effector independent.